2015
DOI: 10.1158/1078-0432.ccr-14-2616
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Relative Interstrand Crosslinker Resistance and PARP Inhibitor Sensitivity in Fanconi Anemia Head and Neck Cancers

Abstract: Purpose Fanconi anemia (FA) is an inherited disorder associated with a constitutional defect in the FA DNA repair machinery that is essential for resolution of DNA interstrand crosslinks. Individuals with FA are predisposed to formation of head and neck squamous cell carcinomas (HNSCCs) at a young age. Prognosis is poor, partly due to patient intolerance of chemotherapy and radiation requiring dose reduction, which may lead to early recurrence of disease. Experimental Design Using HNSCC cell lines derived fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 50 publications
4
24
0
Order By: Relevance
“…[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Mutations in genes associated with transcriptional regulation and cell cycle control that affect DNA repair also have been shown to confer sensitivity to PARPi ( Table 2). [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Clinical data to support this notion that PARPis have more broad antitumor activity has recently been reported with niraparib as maintenance treatment for women with platinum-sensitive, recurrent ovarian cancer. Although women with germline BRAC1/2 mutations and those with HR deficiency benefited the most from treatment with niraparib, women with neither of these predictive features still benefited compared with placebo (PFS of 9.3 months vs 3.9 months; P<.001).…”
Section: Parpis: Early Clinical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Mutations in genes associated with transcriptional regulation and cell cycle control that affect DNA repair also have been shown to confer sensitivity to PARPi ( Table 2). [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Clinical data to support this notion that PARPis have more broad antitumor activity has recently been reported with niraparib as maintenance treatment for women with platinum-sensitive, recurrent ovarian cancer. Although women with germline BRAC1/2 mutations and those with HR deficiency benefited the most from treatment with niraparib, women with neither of these predictive features still benefited compared with placebo (PFS of 9.3 months vs 3.9 months; P<.001).…”
Section: Parpis: Early Clinical Resultsmentioning
confidence: 99%
“…McCabe et al demonstrated this with the discovery that a deficiency in one of several proteins involved in HR (RAD51, RAD54, DSS1, RPA1, NBS1, ataxia telangiectasia and rad3 related [ATR], ataxia telangiectasia mutated [ATM], checkpoint kinase 1 [CHK1], CHK2, Fanconi anemia complementation group D2 [FANCD2], FANCA, and FANCC) induced sensitivity to PARPi . The list of genes that, when mutated, may be involved in HR deficiency continues to expand (Table ) . Mutations in genes associated with transcriptional regulation and cell cycle control that affect DNA repair also have been shown to confer sensitivity to PARPi (Table ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overproduction of HSF2BP sensitized cells to PARPi to a similar extent as to ICL agents. Several reports noted increased sensitivity of FA cells to PARPi: a panel of isogenic chicken DT40 cell mutants (Murai et al, 2012), fibroblast from FA mouse models (McCabe et al, 2006), human and mouse head and neck cancer lines (Lombardi et al, 2015), patient lymphoblastoid lines (Stoepker et al, 2015). However, PARPi sensitivity of core FA proteins and I/D2 is much lower than in BRCA2-deficient cells, and lack of sensitivity was concluded for FA-A, -L, -D2, -I, -J patient lines(Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Therefore, PARP inhibitors may enhance antitumor response after radiation by blocking the DDR of radiation-induced SSBs and DSBs. [16][17][18][19] PARP inhibitors have shown radiosensitizing effects in various cancer cell lines and animal models, [20][21][22][23][24] including HPV+ and HPV− HNSCC cells that differ in their DDR features, 18,19,23,[25][26][27][28][29] and phase I/II clinical trials are underway to test PARP inhibitors administered with radiation or chemotherapy for HNSCC. 9,30 Several small-molecule PARP inhibitors have shown acceptable toxicity when used as monotherapy for patients with solid tumors.…”
Section: Introductionmentioning
confidence: 99%